Neck Circumference as a Marker for Obesity and its Association with Metabolic Syndrome (Academia Journal of Medicine, 2021)
Background: To Study the relationship of measuring neck circumference as a marker for obesity and to assess the association of neck circumfer ence and metabolic syndrome. Subjects and Methods: Patient fulfilling inclusion and exclusion criteria were diagnosed as metabolic syndrome based on criteria. A cut off value of Neck Circumference was calculated and association between increased neck circumference and different parameters of Metabolic Syndrome was evaluated. Results: 23.90% Subjects had normal NC whereas 76.10% had high NC. The mean NC among the study subjects was 38.18±2.43.High NC was seen in 62.79% males and 81.03% females. Mean age of subjects having high NC was 52.04 ±9.82 years. Mean weight for subjects was 78.37 ± 9.45 kgs. Mean BMI for subjects was 33.24 ± 5.62 kg/m2. Mean SBP was 135.21 ± 8.42 mmHg and DBP was 86.08 ± 4.98 mmHg Mean FBG was 144.78 ± 41.02 among subjects with high NC. The mean triglycerides were 163.75 ± 42.19, mean HDL was 38.96 ± 9.42, mean LDL was 114.11 ± 34.66, and mean VLDL was 33.67 ± 8.82.The ROC among the scoring system was found to be highly significant. Overall NC cut off ≥38.0cm was found to be effective for evaluation of metabolic syndrome. In the study population, among males the cutoff value was 38.5 cm while the same was found to be 34.5 cm for females The sensitivity, specificity, positive predictive value and negative predictive value of Neck circumference in the prediction of metabolic syndrome is 87%, 100%,100%, 94% respectively. The accuracy rate of Neck circumference was 84.50%. Conclusion: Neck Circumference was revealed to be a better, simpler and more reliable independent anthropometric measurement as predictor of metabolic syndrome, adiposity and cardiovascular risk than BMI.
Keywords: Neck circumference; Obesity; Metabolic Syndrome